Development of a Method for Measuring Drug Procurement Efficiency Using a Priority Scale Based on Benefit - Cost Ratio Criteria at Pekerja’s General Hospitals in 2023 - Fariha Fariha; Fresley Hutapea; Nofi Erni (Lembaga Pengembangan Kinerja Dosen, 2025)
In Law Number 44 of 2009 concerning Hospitals it is stated that hospitals must meet the requirements for location, buildings, infrastructure, human resources, pharmacy and equipment. Pharmaceutical requirements must ensure the availability of quality, useful, safe and affordable Pharmaceutical Preparations, Medical Devices and Consumable Medical Materials. The Workers' General Hospital has drug procurement data that exceeds the 2022 RKAP target, namely in the last 5 months between August and December 2022. The aim of this research is to reveal empirically the selection of providers by combining three procurement methods, namely e-catalog, direct procurement with the standardization of the Pertamedika IHC Drug Formulary and direct procurement with negotiations carried out by the hospital's own negotiation committee and a priority scale is formed to achieve efficiency targets. This priority scale meets the eligibility test for the Benefit - Cost Ratio criteria. This research was conducted at the Workers' General Hospital in Jakarta. The research time is February 2023 - June 2023. The research approach used is a qualitative approach. Meanwhile, the research method used was a case study in which researchers conducted an in-depth exploration of the process of selecting generic drug providers on a priority scale and tested their feasibility using the Benefit - Cost Ratio (BCR) method. Based on calculations, a BCR value of 1.9 was obtained, which can be interpreted as a priority scale that is feasible for the Workers' General Hospital. The results of this research have implications for hospitals because implementing effective and efficient drug procurement will ensure continuity of service with affordable drug costs.